Economic Diversification in Oil-Exporting Arab Countries. (Policy Papers; Policy Paper ;, 2016)
countries face similar challenges to create jobs and foster more inclusive growth. The current environment of likely durable low oil prices has exacerbated these challenges. The non-oil private sector remains relatively small and, consequently, has been only a limited source of growth and employment. Because oil is an exhaustible resource, new sectors need to be developed so they can take over as the oil and gas industry dwindles. Over-reliance on oil also exacerbates macroeconomic volatility. Greater economic diversification would unlock job-creating growth, increase resilience to oil price volatility and improve prospects for future generations. Macro-economic stability and supportive regulatory and institutional frameworks are key prerequisites for economic diversification...